Latinas in the workplace : an emerging leadership force - López-Mulnix, Esther Elena, 1954- (Journeys to leadership series., 2011)
The subjects of this book - a foundation president, two business CEOs, a doctor, a former college president, a teacher and author, and two school superintendents - grew up with a determination to get educated that was fostered by parents and grandparents. Ingrained in each of them is a sense of honor, the need to treat others with respect, and an inner strength-qualities nurtured by family members. They hope that their stories inspire not only their contemporaries but the next generation of Latinas as well.